2019
DOI: 10.1007/s11136-019-02159-z
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic background and children’s oral health-related quality of life

Abstract: Purpose Ethnic background is known to be related to oral health and socioeconomic position (SEP). In the context of patient-centered oral health care, and the growing number of migrant children, it is important to understand the influence of ethnic background on oral health-related quality of life (OHRQoL). Therefore, we aimed to identify the differences in children’s OHRQoL between ethnic groups, and the contribution of oral health status, SEP, and immigration characteristics. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…OHRQoL is not only affected by oral health conditions, but also related to socio-demographic and contextual factors [ 10 ]. Previous studies showed that children with different demographical backgrounds [ 11 ] (e.g., gender, ethnic background) and family socioeconomical status [ 12 ] had different OHRQoL. The siblings’ number is also a key family characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…OHRQoL is not only affected by oral health conditions, but also related to socio-demographic and contextual factors [ 10 ]. Previous studies showed that children with different demographical backgrounds [ 11 ] (e.g., gender, ethnic background) and family socioeconomical status [ 12 ] had different OHRQoL. The siblings’ number is also a key family characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…Our review included thirteen articles analyzing the oral heath in children/adolescents with age ranging from 0 to 19 years old [39,42,45,46,[48][49][50][51][53][54][55]57,58]. Almost all the studies [39,42,45,46,49,51,54,55] recorded a better oral condition in native children of the control groups compared to the MI groups.…”
Section: Discussionmentioning
confidence: 99%
“…Our review included thirteen articles analyzing the oral heath in children/adolescents with age ranging from 0 to 19 years old [39,42,45,46,[48][49][50][51][53][54][55]57,58]. Almost all the studies [39,42,45,46,49,51,54,55] recorded a better oral condition in native children of the control groups compared to the MI groups. Only Mustafa et al [47] assessed a good knowledge about the importance of oral hygiene among MI parents, showing that they had on average favorable attitudes, subjective norms and strong perception of behavioral control in relation to child tooth brushing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They speak a series of closely related languages such as Tamil, Malayalam, Kannada, and Telugu. It is known that ethnic background is strongly related to socioeconomic position, which has been shown to indirectly influence oral health‐related quality of life 1 . According to the literature, there is ethnic diversity in bodily habits and craniofacial features, including the morphology and morphometry of the mandible and maxillary bones, and upper airway measurements 2–6 .…”
Section: Introductionmentioning
confidence: 99%